2021
DOI: 10.3389/fnmol.2021.811220
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterases in Tripartite Neuromuscular Synapse

Abstract: The neuromuscular junction (NMJ) is a tripartite synapse in which not only presynaptic and post-synaptic cells participate in synaptic transmission, but also terminal Schwann cells (TSC). Acetylcholine (ACh) is the neurotransmitter that mediates the signal between the motor neuron and the muscle but also between the motor neuron and TSC. ACh action is terminated by acetylcholinesterase (AChE), anchored by collagen Q (ColQ) in the basal lamina of NMJs. AChE is also anchored by a proline-rich membrane anchor (PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…However, cells of the left‐most cluster showed a higher transcript count for TUBB3 , and an overall higher number of genes detected than for the other cluster (greyscale, above). Interestingly, the majority of cells (21 out of the 24) presenting a good cDNA profile, expressed Choline Acetyltransferase ( CHAT ), Acetylcholinesterase subunit Q ( COLQ ), and Vesicular Acetylcholine Transporter ( SLC18A3 ), three gene members of the biosynthesis and transport chain of the motor neuron‐specific neurotransmitter acetylcholine 29 . CPLX1 and SCNA , both known to be involved in the modulation of neurotransmitter action and implicated in motor neuron diseases were also expressed by these cells 30,31 .…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cells of the left‐most cluster showed a higher transcript count for TUBB3 , and an overall higher number of genes detected than for the other cluster (greyscale, above). Interestingly, the majority of cells (21 out of the 24) presenting a good cDNA profile, expressed Choline Acetyltransferase ( CHAT ), Acetylcholinesterase subunit Q ( COLQ ), and Vesicular Acetylcholine Transporter ( SLC18A3 ), three gene members of the biosynthesis and transport chain of the motor neuron‐specific neurotransmitter acetylcholine 29 . CPLX1 and SCNA , both known to be involved in the modulation of neurotransmitter action and implicated in motor neuron diseases were also expressed by these cells 30,31 .…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…Interestingly, the majority of cells (21 out of the 24) presenting a good cDNA profile, expressed Choline Acetyltransferase ( CHAT ), Acetylcholinesterase subunit Q ( COLQ ), and Vesicular Acetylcholine Transporter ( SLC18A3 ), three gene members of the biosynthesis and transport chain of the motor neuron‐specific neurotransmitter acetylcholine. 29 CPLX1 and SCNA , both known to be involved in the modulation of neurotransmitter action and implicated in motor neuron diseases were also expressed by these cells. 30 , 31 Furthermore, the cells also expressed FOXP1 and ALDH1A2 , two well‐known embryonic marker genes of developing LMC motor neurons (left most cluster in Figure 4D ).…”
Section: Experimental Procedures and Resultsmentioning
confidence: 99%
“…Despite synaptosomes being widely used as an ex vivo model, there is increasing evidence to support the idea that synapses consist of more than just pre- and postsynaptic terminus ( Chung and Barres, 2012 ; Henstridge et al, 2019 ; Morizawa et al, 2022 ). The tripartite synapse acknowledges the important role that glial cells play in synaptic function: astrocytes, microglia, and oligodendrocytes support synapses within the central nervous system (CNS), and Schwann cells support the neuromuscular junction (NMJ) in the peripheral nervous system ( Perea et al, 2009 ; Petrov et al, 2021 ). Glia have roles crucial for proper synaptic function, including clearance and reuptake of neurotransmitters, Ca 2+ homeostasis, receptor distribution, phagocytosing synaptic material, and synaptogenesis ( Murphy-Royal et al, 2017 ; Um, 2017 ; Kono et al, 2021 ; Shan et al, 2021 ; di Benedetto et al, 2022 ).…”
Section: Studying Synapses At the Molecular Levelmentioning
confidence: 99%
“…But in-depth investigation and research of BuChE, a more important function of BuChE have been proposed, including memory, selective attention, and behavioral response (13,14). Petrov et al (15) and others found that BuChE can be expressed in specific brain areas, such as the amygdala, hippocampus, and frontal lobe, seems to be involved in the development of certain aspects of the nervous system, and expresses nicotinic acetylcholine (ACh) receptors. This suggests that BuChE may regulate the functional state of cells by hydrolyzing the neurotransmitter ACh.…”
Section: Introductionmentioning
confidence: 99%